New solitary wave structures to the (3 - Bulut, Hasan; Aksan, Emine Nesligul; Kayhan, Mirac; Sulaiman, Tukur Abdulkadir (Elsevier, 2019)
The studies of the dynamic behaviors of nonlinear models arising in ocean engineering play a significant role in our daily activities. In this paper, an efficient mathematical technique, namely; the sine-Gordon expansion method is employed to construct the traveling wave solutions to the (3 + 1)-dimensional Kadomtsev-Petviashvili and (3 + 1)-dimensional nonlinear Schrodinger equations. Using suitable values of the parameters, the two- and three-dimensional figures of the obtained solutions are plotted. (C) 2019 Shanghai Jiaotong University. Published by Elsevier B.V.
Keywords: Sine-Gordon expansion method; Kadomtsev-Petviashvili equation; Schrodinger equation; wave solutions